ACTUALIZATION OF EDUCATION IN THE CONDITIONS OF SOCIAL AND ECONOMIC DEVELOPMENT OF NEW UZBEKISTAN - Usmanova , Azizakhon Abdullajonovna (Educational Research in Universal Sciences, 2023)
The work focuses on the conditions for stimulating the economy in order to expand the boundaries of business activity of the population, especially young people, to achieve the principles of competitiveness and the demand for specialists in the labor market. It has been proved that the level of education of the population, its mobile susceptibility to critical comprehension and self-motivation are the favorable criteria for social and economic achievements. State regulatory standards are given that ensure a high-quality level of the educational sphere in New Uzbekistan, positive guidelines for modern forms, types, technologies, innovations of education in the country.